Pain Relief due to Transsacrococcygeal Ganglion Impar Block in Chronic Coccygodynia: A Pilot Study - GÜNDÜZ, OSMAN HAKAN; KENİŞ COŞKUN, ÖZGE; ŞENCAN, SAVAŞ (OXFORD UNIV PRESS, 2015)
ObjectiveCoccygodynia is a distressing condition that presents with pain around the coccyx. Impar (Walther) ganglion is a sympathetic ganglion located at the end of lumbosacral sympathetic chain. The objective of this study is to share our results and follow up of 34 ganglion impar blocks in 22 patients. DesignRetrospective pilot study. SettingInterventional Pain Clinic in the Department of Physical Medicine and Rehabilitation in a university hospital. SubjectsTwenty-two patients with coccygodynia who did not respond to conservative treatment and then presented to interventional pain clinic of a PM&R department in a university hospital MethodsPain was evaluated via 10-cm visual analog scale (VAS). VAS values were obtained before, 1 hour and 3 weeks after injection and during this study was conducted. ResultsFor achieving at least 50% relief of pain, the success rate of a first injection was 82%, but accounted for three technical failures. In patients with a successful outcome, relief lasted for a median duration of 6 months. Relief was reinstated for a median period of 17 months by a second injection in nine patients who presented for repeat treatment. No relief was achieved in two of these patients when they presented for a third treatment. ConclusionsGanglion impar block appears to be effective in patients who have coccygodynia resistant to conservative therapy, with high success rates and prolonged duration of effect. Controlled studies are required to reveal the mechanism of this effect.
Keywords: Coccygodynia; Ganglion Walther; Ganglion Impar; Ganglion Impar Block